The Diversity Visa Lottery: A Study Linking Immigration Politics to Immigrant Characteristics and Experiences - Kremer, Michael S. (Tufts Archival Research Center, 2005)
Every year, 50,000 immigrants obtain Legal Permanent Residency (LPR) in the United States through a program called the Diversity Visa (DV) Lottery. The sole eligibility requirement is that applicants hold a high school degree or have a job that requires at least two years of training, and the lottery is only open to natives of countries that have sent fewer than 50,000 migrants to the U.S. in the past five years. This thesis seeks to contextualize the DV Lottery in the overall scope of U.S. immigration policy and inform the political debate in Congress over the program. Analysis of data from Princeton University's "New Immigrant Survey" shows that, relative to other legal immigrants, DV migrants are younger, more educated, and more likely to speak English well. Six to eighteen months after obtaining LPR, however, they are slightly less likely to be employed than other legal immigrants. That discrepancy between DV migrants' educational backgrounds and likelihood of employment is primarily due to their relative lack of experience in the U.S. Whereas approximately half of all legal immigrants spend time in the U.S. on non-immigrant visas before obtaining LPR, less than 10% of DV migrants had any experience in the U.S. prior to winning the lottery. In Congress, the debate over the program has revolved primarily around the assumption that the lottery encourages increased diversity in the U.S. immigration system at the cost of attracting primarily low-skilled immigrants. The data show, however, that this perceived tradeoff does not actually exist.